Association between preoperative albumin levels and postoperative delirium in geriatric hip fracture patients - Wang, Wei; Yao, Wei; Tang, Wanyun; Li, Yuhao; Lv, Qiaomei; Ding, Wenbo (Frontiers in Medicine, 2024)
Objective This study aims to examine the association between preoperative serum albumin levels and postoperative delirium (POD) in geriatric patients who have undergone hip fracture surgery, with the goal of offering novel insights for clinical interventions targeting POD. Methods A retrospective analysis was conducted on the medical records of patients who underwent hip fracture surgery in a tertiary medical institution from January 2013 to November 2023. The patients were classified based on hypoalbuminemia (defined as a serum albumin level < 35 g/L) and clinical threshold. Multivariable logistic regression and propensity score matching analysis (PSM) were employed to calculate the adjusted odds ratios (OR) and 95% confidence intervals (95% CI) for POD to eliminate potential confounding factors. Additionally, subgroup analysis was performed to explore the interaction effect. Results The retrospective cohort study included 1,440 patients, with an incidence of POD found to be 19.1%. In a multivariable logistic regression analysis, patients with hypoalbuminemia had an adjusted OR of 2.99 (95%CI: 2.14–4.18) compared to those with normal albumin levels (≥ 35 g/L). Furthermore, a significant trend was observed across different severity categories, including mild hypoalbuminemia (34.9–30.0 g/L; adjusted OR = 2.71, 95%CI: 1.84–3.99), moderate hypoalbuminemia (29.9–25.0 g/L, adjusted OR = 3.44, 95%CI: 1.88–6.28), and severe hypoalbuminemia (<25.0 g/L; adjusted OR = 3.97, 95%CI: 1.78–8.86), with a trend value of p <0.001. Similar results were observed in the PSM analysis. Additionally, treating preoperative serum albumin level as a continuous variable, the risk of POD increased by 11% (95% CI, 1.08–1.15) with each 1 g/L decrease in preoperative serum albumin level. Conclusion Low preoperative levels of albumin are strongly associated with POD in geriatric patients with hip fractures, and a significant dose–response relationship exists between them.